Multimodality and compositional metafunction in promotional e-mails - Pordeus, Marcel Pereira (2017)
According to the challenges faced by Linguistics Textual, we can postulatethat the presence of non-verbal elements are fi rm on the agenda of new theoretical challenges to be faced today; as: (BENTES; ALVES FILHO; RAMOS, 2010). With the purpose to accept these challenges and uncover new forms of analysis, it is that this paper was developed. This topic is part of the project: The promotional genre ad email: description of processes and framing of the senses of the text; (Phase I), which focuses on the analysis of reference and multimodal processes in the advertisement of the promotional email. To achieve this purpose, three ads were selected advertiser Hoje Eu Vou, which stresses the multimodal features of the promotional email. For the analysis of data/texts in we support the theoretical concepts of Marcuschi (2003), Wysocki (2004), Bakhtin (1978), Maingueneau (2000), Kress; van Leeuwen (1996) and Lopes-Rossi (2002), authors/ researchers fundamental to achieving the objectives of this research. Aft er the analysis, we see the importance of using multimodal resources for the construction of meanings of the texts, as well as its argumentative function, where we concluded that it is inconceivable disregard the most important part of the visuals in the composition of texts. Still, we cannot disregard the interrelationship between verbal and visual language.